Identification of a framework for implementing ICT in Sri Lankan secondary education system - Tharinda Nishantha Vidanagama; Shashikala Lakshani Karunathilake (Journal of Education and Learning (EduLearn), 2021)
This research work was focused on finding the affected indicators on the barriers to use Information and Communications Technology (ICT) in Sri Lankan Secondary Education System. It also explores a framework to implement ICT in schools overcoming these barriers. In particular, it examined the viewpoint of teachers and principals on the integration of ICT into the schools’ policy in the Western Province of Sri Lanka. Interviews were conducted for 60 secondary school principals and a questionnaire base survey was conducted for 500 teachers of several schools selected from the above pool. What materialized from the analysis showed that, infrastructure facilities, any policies related to the school, Planning and usage of ICT in teaching and learning, Current views held by principals as well as teachers regarding their ICT competencies, Teacher’s fluency of ICT, the perceived viewpoint of teachers and principals regarding the influence and subsequent function of ICT in education has an influence on the magnitude of ICT usage in schools. According to the analyzed data, a framework was designed to make readiness and maintain smooth Teaching and Learning system in secondary schools. Finally, the research has collected feedback from involved parties during the implementation process to evaluate competency of the suggested framework.